Non-aqueous electrolyte secondary battery
Patent Information
- Application Number
- CN202280050930.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-07-29
- Filing Date
- 2022-06-23
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-06-23
AI Technical Summary
[0015]根据本发明的非水电解质二次电池,能够提高循环特性。
Smart Images

Figure CN117730444B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to non-aqueous electrolyte secondary batteries. Background Technology
[0002] Non-aqueous electrolyte secondary batteries, which consist of wound electrodes (positive and negative electrodes separated by spacers) housed in a metal casing, have long been widely used. The spacers prevent short circuits caused by contact between the positive and negative electrodes.
[0003] Patent Document 1 discloses the following technology: two coating layers are stacked on the surface of a substrate layer that is a porous substrate, such that the content of binder in the coating layer on the surface side is higher than the content of binder in the coating layer on the substrate side, thereby ensuring the safety of the battery and improving the tightness between the spacer and the electrode.
[0004] Patent document 2 discloses the following technology: a layer is laminated on both sides of the substrate layer that serves as a microporous membrane, such that the content of the binder in the coating layer disposed on the negative electrode side is higher than the content of the binder in the coating layer disposed on the positive electrode side, thereby preventing the battery from running out of control at high temperatures.
[0005] Existing technical documents
[0006] Patent documents
[0007] Patent Document 1: Japanese Patent Application Publication No. 2013-235824
[0008] Patent Document 2: Japanese Patent Application Publication No. 2015-88430 Summary of the Invention
[0009] The problem that the invention aims to solve
[0010] However, in secondary batteries, suppressing the reduction in battery capacity caused by repeated charge-discharge cycles and improving cycle characteristics are important issues. The inventors of this application have conducted in-depth research and have determined that in wound electrode bodies, the charge-discharge reaction is difficult to occur uniformly on the inside and outside of the positive electrode, thus easily leading to a decrease in cycle characteristics. It is speculated that this is because the amount of electrolyte held on the inside of the positive electrode is less than the amount held on the outside. The technologies disclosed in Patent Documents 1 and 2 do not consider the decrease in cycle characteristics caused by the difference in electrolyte retention on the inside and outside of the positive electrode, and there is still room for improvement.
[0011] The purpose of this invention is to provide a non-aqueous electrolyte secondary battery that improves cycle characteristics.
[0012] Methods for solving problems
[0013] A non-aqueous electrolyte secondary battery, as an embodiment of the present invention, is characterized by comprising: a wound electrode body formed by winding a positive electrode and a negative electrode with a first spacer disposed inside the positive electrode and a second spacer disposed outside the positive electrode; an electrolyte; and an outer casing that houses the electrode body and the electrolyte. The first spacer has a first substrate layer and a first coating layer formed on the surface of the first substrate layer opposite to the positive electrode. The second spacer has a second substrate layer and a second coating layer formed on the surface of the second substrate layer opposite to the positive electrode. The first coating layer and the second coating layer each contain a filler and an organic material, and the filler content in the first coating layer is greater than the filler content in the second coating layer.
[0014] Invention Effects
[0015] The non-aqueous electrolyte secondary battery according to the present invention can improve cycle characteristics. Attached Figure Description
[0016] Figure 1 This is a longitudinal cross-sectional view of a cylindrical battery as an example of an implementation method.
[0017] Figure 2 yes Figure 1 The diagram shows a cross-sectional view of the wound electrode body contained in the cylindrical battery. Detailed Implementation
[0018] Hereinafter, an example embodiment of the non-aqueous electrolyte secondary battery of the present invention will be described in detail with reference to the accompanying drawings. The following example illustrates a cylindrical battery in which a wound electrode body is housed within a cylindrical outer casing; however, the outer casing is not limited to a cylindrical shape and may be, for example, square, coin-shaped, etc. Alternatively, the outer casing may be a pouch-shaped form composed of a laminate containing a metal layer and a resin layer. It should be noted that in the following description, specific shapes, materials, values, orientations, etc., are examples used to facilitate understanding of the present invention and may be appropriately varied depending on the specifications of the non-aqueous electrolyte secondary battery. Furthermore, in the following description, where multiple embodiments and modifications are included, it is initially envisioned that their characteristic features be appropriately combined.
[0019] Figure 1 This is a longitudinal cross-sectional view of a cylindrical battery 10 as an example of an implementation method. Figure 1The cylindrical battery 10 shown houses the electrode body 14 and electrolyte (not shown) within the outer casing 15. The electrode body 14 has a wound structure formed by winding a strip-shaped positive electrode 11 and a negative electrode 12 with a first spacer 13a disposed on the inner side of the positive electrode 11 and a second spacer 13b disposed on the outer side of the positive electrode 11. It should be noted that, for ease of explanation, the axial direction of the outer casing 15 will be referred to as "longitudinal or vertical direction," the sealing body 16 side as "upper," and the bottom side of the outer casing 15 as "lower." It should be noted that the winding axis direction of the electrode body 14 is approximately aligned with the axial direction of the outer casing 15. Furthermore, the direction perpendicular to the axial direction of the outer casing 15 will be referred to as "lateral or radial," the radial center side of the outer casing 15 as "inner side," and the radial outer side as "outer side."
[0020] As a non-aqueous solvent (organic solvent) for the electrolyte, carbonates, lactones, ethers, ketones, esters, etc., can be used, and two or more of these solvents can be mixed. When using two or more solvents in combination, a mixed solvent containing cyclic carbonates and chain carbonates is preferred. For example, as cyclic carbonates, ethylene carbonate (EC), propylene carbonate (PC), butyl carbonate (BC), etc., can be used; as chain carbonates, dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC), etc., can be used. As esters, methyl acetate (MA) and methyl propionate (MP), etc., are preferred. The non-aqueous solvent may contain halogen-substituted products formed by replacing at least a portion of the hydrogen atoms of these solvents with halogen atoms such as fluorine. As halogen-substituted products, fluoroethylene carbonate (FEC) and fluoromethyl propionate (FMP), etc., are preferred, for example. Electrolyte salts used as electrolytes include LiPF6, LiBF4, LiCF3SO3, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, and mixtures thereof. The solubility of the electrolyte salt relative to a non-aqueous solvent is, for example, 0.5 mol / L to 2.0 mol / L.
[0021] The interior of the cylindrical battery 10 is sealed by blocking the opening of the outer casing 15 with the sealing body 16. Insulating plates 17 and 18 are respectively provided above and below the electrode body 14. The positive electrode lead 19 extends upward from the upper end face of the electrode body 14 through the through hole of the insulating plate 17 and is welded to the lower surface of the filter 22, which serves as the bottom plate of the sealing body 16. In the cylindrical battery 10, the top plate, i.e., the cover 26, of the sealing body 16, which is electrically connected to the filter 22, becomes the positive terminal. On the other hand, the negative electrode lead 20 extends from the lower end face of the electrode body 14 through the outside of the insulating plate 18 to the bottom side of the outer casing 15 and is welded to the inner bottom surface of the outer casing 15. In the cylindrical battery 10, the outer casing 15 becomes the negative terminal.
[0022] The outer casing 15 is, for example, a bottomed cylindrical metal can. A gasket 27 is provided between the outer casing 15 and the sealing body 16 to ensure the airtightness of the interior of the cylindrical battery 10. The outer casing 15 has, for example, an inlet portion 21 formed by stamping the side portion from the outside. The inlet portion 21 is preferably formed in a ring shape along the circumference of the outer casing 15, and the sealing body 16 is supported on its upper surface by the gasket 27.
[0023] The sealing body 16 comprises a filter 22, a lower valve body 23, an insulating member 24, an upper valve body 25, and a cover 26, stacked sequentially from the electrode body 14 side. Each component constituting the sealing body 16 has, for example, a circular or annular shape, and all components except the insulating member 24 are electrically connected to each other. The lower valve body 23 and the upper valve body 25 are connected to each other at their respective central portions, with the insulating member 24 sandwiched between their respective peripheral portions. If the internal pressure of the battery rises due to abnormal heating, for example, the lower valve body 23 breaks, causing the upper valve body 25 to expand towards the cover 26 and separate from the lower valve body 23, thereby severing the electrical connection between them. If the internal pressure rises further, the upper valve body 25 breaks, and gas is discharged from the through-hole 26a of the cover 26.
[0024] The following is for reference Figure 2 The electrode body 14 will be described in detail. Figure 2 yes Figure 1 The diagram shows a cross-sectional view of the wound electrode body 14 included in the cylindrical battery 10. In the electrode body 14, a first spacer 13a is disposed inside the wound of the positive electrode 11, and a second spacer 13b is disposed outside the wound of the positive electrode 11. The negative electrode 12, the first spacer 13a, the positive electrode 11, and the second spacer 13b are all formed in a strip shape, and are overlapped in this order and wound into a spiral shape around a winding axis that serves as the winding center of the electrode body 14, thus achieving a state of alternating stacking in the radial direction of the electrode body 14. In the electrode body 14, the length direction of the positive electrode 11 and the negative electrode 12 is the winding direction, and the width direction of the positive electrode 11 and the negative electrode 12 is the winding axis direction. It should be noted that "inner side of the roll" refers to the inner radial direction (winding axis side) of the electrode body 14, and "outer side of the roll" refers to the outer radial direction of the electrode body 14.
[0025] The positive electrode 11 has a positive current collector and a positive electrode flux layer formed on the surface of the positive current collector. The positive current collector can be a foil of a metal that is stable within the potential range of the positive electrode, such as aluminum, or a film with the metal disposed on the surface. The thickness of the positive current collector is, for example, 10 μm to 30 μm.
[0026] The positive electrode mixture layer is preferably formed on both sides of the positive electrode current collector. The thickness of the positive electrode mixture layer is, for example, 10 μm to 150 μm per side of the positive electrode current collector. The positive electrode mixture layer contains, for example, a positive electrode active material, a conductive agent, and a binder. The positive electrode can be produced, for example, by applying a positive electrode mixture slurry containing the positive electrode active material, the conductive agent, the binder and the like onto both sides of the positive electrode current collector, drying the coating film, and then rolling the coating film with a roller or the like.
[0027] Examples of the positive electrode active material contained in the positive electrode mixture layer include lithium transition metal oxides containing transition metal elements such as Co, Mn, and Ni. The lithium transition metal oxide is, for example, Li x CoO2, Li x NiO2, Li x MnO2, Li x Co y Ni 1-y O2, Li x Co y M 1-y O z , Li x Ni 1-y M y O z , Li x Mn2O4, Li x Mn 2-y M y O4, LiMPO4, Li2MPO4F (M is at least one selected from Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B, 0<x≤1.2, 0<y≤0.9, 2.0≤z≤2.3). These may be used alone or in combination of two or more. From the viewpoint of enabling high capacity of the non-aqueous electrolyte secondary battery, the positive electrode active material preferably contains Li x NiO2, Li x Co y Ni 1-y O2, Li x Ni 1-y M y O z (M is at least one selected from Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B, 0<x≤1.2, 0<y≤0.9, 2.0≤z≤2.3) and other lithium-nickel composite oxides.
[0028] Examples of the conductive agent contained in the positive electrode mixture layer include carbon-based particles such as carbon black (CB), acetylene black (AB), Ketjen black, carbon nanotube (CNT), graphene, and graphite. These may be used alone or in combination of two or more.
[0029] Examples of the binder contained in the positive electrode mixture layer include fluorine-based resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyimide-based resins, acrylic resins, polyolefin-based resins, and the like. These may be used alone, or two or more thereof may be used in combination.
[0030] The negative electrode 12 has a negative electrode current collector and a negative electrode mixture layer formed on the surface of the negative electrode current collector. For the negative electrode current collector, a foil of a metal that is stable within the potential range of the negative electrode such as copper, a film having the metal arranged on its surface layer, or the like can be used. The thickness of the negative electrode current collector is, for example, 5 μm to 30 μm.
[0031] The negative electrode mixture layer is preferably formed on both sides of the negative electrode current collector. The thickness of the negative electrode mixture layer is, for example, 10 μm to 150 μm on one side of the negative electrode current collector. The negative electrode mixture layer contains, for example, a negative electrode active material and a binder. The negative electrode can be produced, for example, by applying a negative electrode mixture slurry containing the negative electrode active material, the binder and the like onto both sides of the negative electrode current collector, drying the coating film, and then rolling the coating film using a roll or the like.
[0032] The negative electrode active material contained in the negative electrode mixture layer is not particularly limited as long as it can reversibly occlude and release lithium ions, and a carbon material such as graphite is usually used. The graphite may be any of natural graphite such as flake graphite, massive graphite and earthy graphite, and artificial graphite such as massive artificial graphite and graphitized mesophase carbon microbeads. In addition, as the negative electrode active material, metals that form an alloy with Li such as Si and Sn, metal compounds containing Si, Sn and the like, lithium-titanium composite oxides and the like can be used. For example, SiO x A Si-containing compound represented by (0.5≤x≤1.6), or Li 2y SiO (2+y) A Si-containing compound in which fine Si particles are dispersed in a lithium silicate phase represented by (0<y<2) and the like can be used in combination with graphite.
[0033] Examples of the binder contained in the negative electrode mixture layer include styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber (NBR), carboxymethyl cellulose (CMC) or a salt thereof, polyacrylic acid (PAA) or a salt thereof (PAA-Na, PAA-K and the like, which may also be a partially neutralized salt), polyvinyl alcohol (PVA), and the like. These may be used alone, or two or more thereof may be used in combination.
[0034] As Figure 2As shown, the first spacer 13a is disposed inside the roll of the positive electrode 11, and the second spacer 13b is disposed outside the roll of the positive electrode 11. That is, in the electrode body 14, the first spacer 13a is disposed such that it is sandwiched between the radially inner negative electrode 12 and the radially outer positive electrode 11, and the second spacer 13b is disposed such that it is sandwiched between the radially inner positive electrode 11 and the radially outer negative electrode 12. The first spacer 13a and the second spacer 13b, by being located between the positive electrode 11 and the negative electrode 12, physically and electrically separate the positive electrode 11 and the negative electrode 12.
[0035] The first spacer 13a has a first substrate layer 30 and a first coating layer 32 formed on the surface of the first substrate layer 30 opposite to the positive electrode 11, and the second spacer 13b has a second substrate layer 34 and a second coating layer 36 formed on the surface of the second substrate layer 34 opposite to the positive electrode 11.
[0036] For example, porous substrates with ion permeability and insulation properties are used as the first substrate layer 30 and the second substrate layer 34. Specific examples of porous substrates include microporous films, woven fabrics, and nonwoven fabrics. Examples of materials for the first substrate layer 30 and the second substrate layer 34 include polyethylene, polypropylene, copolymers of polyethylene and α-olefins, acrylic resins, polystyrene, polyester, cellulose, etc. The thickness of the first substrate layer 30 and the second substrate layer 34 is, for example, 3 μm to 20 μm.
[0037] The first coating layer 32 and the second coating layer 36 respectively contain fillers and organic materials, with the filler content in the first coating layer 32 being greater than that in the second coating layer 36. Here, the filler content in the first coating layer 32 is the ratio of the mass of the filler contained in the first coating layer 32 to the mass of the first coating layer 32, and the filler content in the second coating layer 36 is the ratio of the mass of the filler contained in the second coating layer 36 to the mass of the second coating layer 36.
[0038] The filler has a high affinity for the electrolyte, therefore, the first coating layer 32 has better electrolyte retention compared to the second coating layer 36. By placing the first coating layer 32 on the inside of the positive electrode 11 roll and the second coating layer 36 on the outside of the positive electrode 11 roll, the difference in electrolyte retention between the inside and outside of the positive electrode 11 roll can be reduced, thus improving cycle performance.
[0039] The filler content in the first coating layer 32 is preferably 75% by mass or more, more preferably 85% by mass or more. Furthermore, the upper limit of the filler content in the first coating layer 32 is, for example, 95% by mass.
[0040] The filler content in the second coating layer 36 is preferably 60% by mass or less, more preferably 50% by mass or less. Furthermore, the lower limit of the filler content in the second coating layer 36 is, for example, 10% by mass.
[0041] The thicknesses of the first coating layer 32 and the second coating layer 36 are not particularly limited, for example, 1 μm to 10 μm respectively. In addition, the method of forming the first coating layer 32 and the second coating layer 36 is not particularly limited, for example, the coating layers can be formed on the main surface of at least one of the first substrate layer 30 and the second substrate layer 34 using a blade coating method, a gravure coating method, a transfer printing method or a mold coating method.
[0042] The fillers included in the first coating layer 32 and the second coating layer 36 preferably have a melting point or thermal softening point of 150°C or higher, more preferably 200°C or higher. This provides a heat shrinkage suppression effect on the spacer. Examples of fillers include metal oxide particles, metal nitride particles, metal fluoride particles, metal carbide particles, and sulfide particles. Examples of metal oxide particles include aluminum oxide (e.g., α-Al₂O₃), titanium oxide, magnesium oxide, zirconium oxide, nickel oxide, silicon oxide, and manganese oxide. Examples of metal nitride particles include titanium nitride, boron nitride, aluminum nitride, magnesium nitride, and silicon nitride. Examples of metal fluoride particles include aluminum fluoride, lithium fluoride, sodium fluoride, magnesium fluoride, calcium fluoride, and barium fluoride. Examples of metal carbide particles include silicon carbide, boron carbide, titanium carbide, and tungsten carbide. Examples of sulfide particles include barium sulfate. Alternatively, the filler can be zeolite (M 2 / n Porous aluminosilicates such as O·Al₂O₃·xSiO₂·yH₂O, where M is a metallic element, x≥2, y≥0, and talc (Mg₃Si₄O₂) ... are composed of O·Al₂O₃·xSiO₂·yH₂O. 10 Layered silicates such as (OH)2, barium titanate (BaTiO3), strontium titanate (SrTiO3), and other minerals. They can be used alone or in combination of two or more.
[0043] The BET specific surface area of the packing is not particularly limited, but is preferably 1m². 2 / g~20m 2 The range of / g is more preferably 3m. 2 / g~15m 2 The range is / g. The average particle size of the filler is not particularly limited, but is preferably 0.1μm to 5μm, more preferably 0.2μm to 1μm.
[0044] Organic materials are materials capable of forming films on a substrate layer. Furthermore, organic materials preferably possess the function of bonding individual fillers to each other and to the substrate layer. Organic materials are preferably polymeric materials, such as fluorinated resins like polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE), polyimide resins, polyamide resins, acrylic resins, polyolefin resins, styrene-butadiene rubber (SBR), nitrile rubber (NBR), carboxymethyl cellulose (CMC) or its salts, polyacrylic acid (PAA) or its salts, and polyvinyl alcohol (PVA). They can be used alone or in combination of two or more.
[0045] Example
[0046] The present invention will be further illustrated below by way of examples, but the present invention is not limited to these examples.
[0047] <Example 1>
[0048] [The production of the positive electrode]
[0049] LiNi is used as the positive electrode active material. 0.88 Co 0.09 Al 0.03 The O2 represents aluminum-containing lithium nickel cobalt oxide. 98 parts by weight of LiNi 0.88 Co 0.09 Al 0.03 O2, 1 part by mass of acetylene black, and 1 part by mass of polyvinylidene fluoride (PVDF, average molecular weight 1.1 million) are mixed, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) is added to prepare a positive electrode slurry. Next, this positive electrode slurry is coated onto both sides of a strip-shaped positive electrode current collector formed from 15 μm thick aluminum foil. After drying, it is calendered and cut into specified electrode plate sizes to create a positive electrode with a positive electrode slurry layer formed on both sides of the positive electrode current collector. An exposed positive electrode portion, lacking the slurry layer and exposed on the current collector surface, is formed approximately at the center of the positive electrode's length. An aluminum positive electrode lead is soldered to the exposed positive electrode portion.
[0050] [Making the negative electrode]
[0051] A negative electrode slurry was prepared by mixing 95 parts by weight of graphite, 5 parts by weight of Si oxide, 1 part by weight of carboxymethyl cellulose (CMC), and 1.2 parts by weight of styrene-butadiene rubber (SBR) with an appropriate amount of water. Next, this negative electrode slurry was coated onto both sides of a strip-shaped negative electrode current collector formed from 8 μm thick copper foil. After drying, it was calendered and cut into specified electrode plate sizes to create a negative electrode with a negative electrode slurry layer formed on both sides of the negative electrode current collector. A negative electrode exposed portion, lacking the slurry layer and exposed on the current collector surface, was formed at the outer end of the negative electrode roll. A nickel-plated negative electrode lead was soldered to the negative electrode exposed portion.
[0052] [Making Spacer A]
[0053] A porous polyethylene substrate with a thickness of 12 μm was used as the substrate layer. α-Al₂O₃ powder (as filler) and an acrylate-based binder emulsion (as organic material) were mixed at a solids content mass ratio of 95:5. A suitable amount of water was then added to achieve a solids content concentration of 10% by mass, preparing dispersion A. Dispersion A was coated onto the entire surface of one side of the porous substrate using a microgravure coating machine. After drying, a coating layer A with an average thickness of 4 μm was formed on one side of the substrate.
[0054] [Making Spacer B]
[0055] A porous polyethylene substrate with a thickness of 12 μm was used as the substrate layer. Terephthaloyl chloride (TPC) was added to a solution containing p-phenylenediamine and calcium chloride dissolved in NMP to polymerize the para-aromatic polyamide, resulting in a para-aromatic polyamide solution with a solid content concentration of 2% by mass. The α-Al₂O₃ powder (as filler) and the para-aromatic polyamide solution were mixed in a 50:50 mass ratio to prepare dispersion B. Dispersion B was coated onto the entire surface of one side of the porous substrate using a microgravure coating machine, and the coating was dried to form a coating layer B with an average thickness of 4 μm on one side of the substrate.
[0056] [Preparation of Electrolyte]
[0057] Five parts by mass of vinylene carbonate (VC) are added to 100 parts by mass of a mixed solvent consisting of ethylene carbonate (EC) and dimethyl carbonate (DMC) (EC:DMC = 1:3 by volume). LiPF6 is dissolved in this mixed solvent to a concentration of 1 mol / L to prepare an electrolyte.
[0058] [Making a Secondary Battery]
[0059] A spiral electrode body is fabricated by winding the positive and negative electrodes together, with spacer A (serving as a first spacer) and spacer B (serving as a second spacer) separating them. Spacer A is positioned inside the spiral of the positive electrode with coating layer A facing the positive electrode, and spacer B is positioned outside the spiral with coating layer B facing the positive electrode. Insulating plates are placed above and below the electrode body, and the electrode body is housed within an outer casing. The negative electrode lead is soldered to the bottom of the bottomed cylindrical outer casing, and the positive electrode lead is soldered to a sealing body. Electrolyte is injected into the outer casing, and the opening of the outer casing is sealed with a sealing body through a gasket, thus fabricating a secondary battery.
[0060] [Evaluation of Capacity Maintenance Rate]
[0061] The aforementioned secondary battery was charged at a constant current of 0.1 It at 25°C until the battery voltage reached 4.2V, then charged at a constant voltage of 4.2V until the current reached 0.05 It. Next, it was discharged at a constant current of 0.5 It until the battery voltage reached 2.5V. This charge-discharge cycle was considered one cycle, and 500 cycles were performed. The capacity retention rate of the secondary battery during the charge-discharge cycle was calculated using the following formula.
[0062] Capacity retention rate = (Discharge capacity at 500th cycle / Discharge capacity at 1st cycle) × 100
[0063] <Example 2>
[0064] [Making Spacer C]
[0065] A porous polyethylene substrate with a thickness of 12 μm was used as the substrate layer. α-Al₂O₃ powder (as filler) and an acrylate-based binder emulsion (as organic material) were mixed at a solids content mass ratio of 85:15. Water was then added to a concentration of 10% by mass to prepare dispersion C. Dispersion C was coated onto the entire surface of one side of the porous substrate using a microgravure coating machine. After drying, a coating layer C with an average thickness of 4 μm was formed on one side of the substrate.
[0066] In the fabrication of the secondary battery, spacer C is used as the first spacer. The spacer C is disposed on the inner side of the positive electrode in such a way that the coating layer C is opposite to the positive electrode. Otherwise, the secondary battery is fabricated in the same manner as in Example 1, and the capacity retention rate is evaluated.
[0067] <Comparative Example 1>
[0068] In the fabrication of the secondary battery, spacer C is used as the first spacer and the second spacer. The spacer C is arranged on the inner side and the outer side of the positive electrode in such a way that the coating layer C of either spacer is opposite to the positive electrode. Otherwise, the secondary battery is fabricated in the same manner as in Example 1, and the capacity retention rate is evaluated.
[0069] <Comparative Example 2>
[0070] In the fabrication of the secondary battery, spacer B is used as the first spacer, and spacer B is disposed on the inner side of the positive electrode roll with coating layer B facing the positive electrode. Spacer A is used as the second spacer, and spacer A is disposed on the outer side of the positive electrode roll with coating layer A facing the positive electrode. Otherwise, the secondary battery is fabricated in the same manner as in Example 1, and the capacity retention rate is evaluated.
[0071] <Comparative Example 3>
[0072] In the fabrication of the secondary battery, spacer B is used as the first spacer, and spacer B is disposed on the inner side of the positive electrode roll with coating layer B facing the positive electrode. Spacer C is used as the second spacer, and spacer C is disposed on the outer side of the positive electrode roll with coating layer C facing the positive electrode. Otherwise, the secondary battery is fabricated in the same manner as in Example 1, and the capacity retention rate is evaluated.
[0073] The evaluation results of the secondary batteries of the examples and comparative examples are recorded in Table 1. In addition, the filler content in the first coating layer and the second coating layer are also recorded in Table 1.
[0074] [Table 1]
[0075]
[0076] Compared to the comparative example, the secondary battery of the embodiment exhibits higher capacity retention and improved cycle characteristics. This is presumably because, by increasing the filler content in the first coating layer (opposite to the positive electrode on the inside of the roll) to a higher content in the second coating layer (opposite to the positive electrode on the outside of the roll), the electrolyte retention on the inside of the positive electrode is improved, thereby enhancing the uniformity of the charge-discharge reaction on both sides of the positive electrode.
[0077] Explanation of reference numerals in the attached figures
[0078] 10: Cylindrical battery; 11: Positive electrode; 12: Negative electrode; 13a: First spacer; 13b: Second spacer; 14: Electrode body; 15: Outer body; 16: Sealing body; 17, 18: Insulating plate; 19: Positive electrode lead; 20: Negative electrode lead; 21: Inlet; 22: Filter; 23: Lower valve body; 24: Insulating component; 25: Upper valve body; 26: Cover; 27: Gasket; 30: First substrate layer; 32: First coating layer; 34: Second substrate layer; 36: Second coating layer.
Claims
1. A non-aqueous electrolyte secondary battery, comprising: A wound electrode body is formed by winding a positive electrode and a negative electrode with a first spacer disposed inside the positive electrode and a second spacer disposed outside the positive electrode. Electrolyte; and An outer casing that houses the electrode body and the electrolyte. The first spacer has a first substrate layer and a first coating layer formed on the surface of the first substrate layer opposite to the positive electrode. The second spacer has a second substrate layer and a second coating layer formed on the surface of the second substrate layer opposite to the positive electrode. The first coating layer and the second coating layer each contain fillers and organic materials. The filler is selected from at least one of metal oxide particles, metal nitride particles, metal fluoride particles, metal carbide particles, and sulfide particles. The filler content in the first coating layer is greater than the filler content in the second coating layer.
2. The non-aqueous electrolyte secondary battery according to claim 1, wherein, The filler content in the first coating layer is 75% by mass or more, and the filler content in the second coating layer is 60% by mass or less.
Citation Information
Patent Citations
Separator and method of manufacturing the same, and lithium secondary battery including the separator
JP2013235824A
Nonaqueous electrolyte secondary battery separator, and nonaqueous electrolyte secondary battery having the same
JP2015088430A
Nonaqueous secondary battery, and manufacturing method thereof
JP2011090917A
Nonaqueous electrolyte secondary battery
JP2011181493A